Indole derivatives, microbiome and graft versus host disease. (June 2021) - Qayed, Muna; Michonneau, David; Socié, Gerard; Waller, Edmund K
Highlights: Microbiota and their metabolites maintain immune homeostasis within the gut. Aryl hydrocarbon receptor ligands, or indoles, modulate innate and adaptive immunity. Indoles improve gut barrier integrity and protect against graft versus host disease. Abstract : Graft versus host disease is a life-threatening complication following allogeneic hematopoietic stem cell transplantation driven by donor T cells reacting against disparate host antigens. Immune homeostasis within the gut plays a major role in the graft versus host response. Gut microbiota and its metabolites impact gut integrity, inflammation and immune activation within the gut. This review will focus on the role of indoles, a product of microbiota metabolism, on gut homeostasis and our current understanding on how that modulates graft versus host disease.